Transient Receptor Potential Vanilloid 1 Function at Central Synapses in Health and Disease - Meza, Rodrigo C.; Ancatén-González, Carlos; Chiu, Chiayu Q.; Chávez, Andrés E. (Frontiers in Cellular Neuroscience, 2022)
The transient receptor potential vanilloid 1 (TRPV1), a ligand-gated nonselective cation channel, is well known for mediating heat and pain sensation in the periphery. Increasing evidence suggests that TRPV1 is also expressed at various central synapses, where it plays a role in different types of activity-dependent synaptic changes. Although its precise localizations remain a matter of debate, TRPV1 has been shown to modulate both neurotransmitter release at presynaptic terminals and synaptic efficacy in postsynaptic compartments. In addition to being required in these forms of synaptic plasticity, TRPV1 can also modify the inducibility of other types of plasticity. Here, we highlight current evidence of the potential roles for TRPV1 in regulating synaptic function in various brain regions, with an emphasis on principal mechanisms underlying TRPV1-mediated synaptic plasticity and metaplasticity. Finally, we discuss the putative contributions of TRPV1 in diverse brain disorders in order to expedite the development of next-generation therapeutic treatments.